1985
DOI: 10.1016/0014-5793(85)81081-4
|View full text |Cite
|
Sign up to set email alerts
|

An electrogenic uniport mediates light‐dependent Ca2+ influx into intact spinach chloroplasts

Abstract: Light-dependent Ca2+ influx into intact spinach chloroplasts, measured with the metallochromic indicator arsenazo III, is stimulated by uncouplers (FCCP, CCCP, nigericin) and inhibited by ruthenium red. The data presented demonstrate that light-dependent Ca 2+ influx into chloroplasts is electrogenic and mediated by a uniport-type carrier. The characteristics of the carrier system are similar to those of the Caz+ uniport of mitochondria.Spinach Chloroplast Ca2+

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 31 publications
3
28
0
1
Order By: Relevance
“…Several years later, when it was apparent that plant cells maintained very low [Ca 21 ] i, the role of the chloroplast in the regulation of this ion received further attention. Different laboratories using chloroplasts from wheat (Muto et al, 1982) and spinach (Kreimer et al, 1985a(Kreimer et al, , 1985b confirmed the dramatic light-dependent uptake of Ca 21 . Kreimer et al (1985aKreimer et al ( , 1985b further concluded that photosynthetic electron transport was essential and that it was the membrane potential rather than pH that drove Ca 21 uptake.…”
Section: Ca 21 and Chloroplastsmentioning
confidence: 85%
“…Several years later, when it was apparent that plant cells maintained very low [Ca 21 ] i, the role of the chloroplast in the regulation of this ion received further attention. Different laboratories using chloroplasts from wheat (Muto et al, 1982) and spinach (Kreimer et al, 1985a(Kreimer et al, , 1985b confirmed the dramatic light-dependent uptake of Ca 21 . Kreimer et al (1985aKreimer et al ( , 1985b further concluded that photosynthetic electron transport was essential and that it was the membrane potential rather than pH that drove Ca 21 uptake.…”
Section: Ca 21 and Chloroplastsmentioning
confidence: 85%
“…To investigate whether light-induced Ca>2 influx causes the stimulation of FBPase activation, we also examined the effect of ruthenium red, an inhibitor of light-induced Ca2+ influx (11), on activation of FBPase (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…After Chl and Protein Determination. Chl and protein was determined as previously described (11,13).…”
Section: Methodsmentioning
confidence: 99%
“…Photosynthetic intermediates (7), calcium (22,23), and diacylglycerol (21) are putative candidates for second messengers. The vanadate sensitivity of blue light-stimulated proton pumping also implicates a H+-ATPase at the guard cell plasma membrane (24).…”
Section: Discussionmentioning
confidence: 99%